2015
DOI: 10.1002/gps.4368
|View full text |Cite
|
Sign up to set email alerts
|

White matter microstructural damage and depressive symptoms in patients with mild cognitive impairment and cerebral small vessel disease: the VMCI‐Tuscany Study

Abstract: These results outline the presence of an association between WM microstructural damage and depressive symptoms in MCI patients with SVD. This relationship does not seem to be mediated by disability, cognitive, and motor impairment, thus supporting the vascular depression hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 35 publications
0
15
1
Order By: Relevance
“…The association with depressive symptoms is stronger for the MCI subtype with memory impairment [79], but this was independent of underlying vascular disease [8082]. Some studies suggested an association between white matter microstructural damage and depressive symptoms in MCI patients with small vessel disease [74, 83], whereas others showed no association between depressive symptoms and the rate of incident MCI [84]. The path from CVD to VaDep and to vascular dementia appears to be likely reciprocal and not direct or sequential [85], whereas others suggested that depression is an independent risk factor for subsequent vascular dementia [86].…”
Section: Resultsmentioning
confidence: 99%
“…The association with depressive symptoms is stronger for the MCI subtype with memory impairment [79], but this was independent of underlying vascular disease [8082]. Some studies suggested an association between white matter microstructural damage and depressive symptoms in MCI patients with small vessel disease [74, 83], whereas others showed no association between depressive symptoms and the rate of incident MCI [84]. The path from CVD to VaDep and to vascular dementia appears to be likely reciprocal and not direct or sequential [85], whereas others suggested that depression is an independent risk factor for subsequent vascular dementia [86].…”
Section: Resultsmentioning
confidence: 99%
“…In this large cohort, the microstructural integrity of both WMH and NAWM was related to global cognitive function, memory, and executive function. 33 Moreover, TBSS postprocessing analyses were performed and corpus callosum especially in the genu and splenium showed the highest significant relation with global cognitive index. Analyses for each cognitive domain showed the strongest relationship between (1) cingulum bundle microstructural integrity and verbal memory performance and (2) frontal WM and psychomotor speed.…”
Section: June 2016mentioning
confidence: 99%
“…The etiology of depression is incompletely understood, whereas evidence suggests a “vascular depression” hypothesis ( 2 ). Several studies have indicated that cerebral small vessel disease (CSVD) might play an important role in the etiologic factors of depression ( 3 5 ).…”
Section: Introductionmentioning
confidence: 99%